THE EFFECT OF EXPERIENCE, GENERALIZATION, REINFORCEMENT, AND APPLICATION (EGRA) TECHNIQUE ON STUDENTS’ ABILITY IN COMPREHENDING RECOUNT TEXT AT THE TENTH GRADE STUDENTS OF MAS MADINATUSSALAM - Ritonga, Aula Adnin (BRIGHT VISION Journal of Language and Education, 2021)
This research was conducted to know the effect of EGRA technique on students’ ability in comprehending recount text at the tenth grade students of MAS Madinatussalam. The research was quantitative research with quasi experimental design by choosing one group pre-post test design. There was only one class which consisted of 31 students as the sample of research. The data were gained based on the students’ score in pre and post test, and the data calculated by SPSS 17.0 to determine the data normality, data homogeneity, and the hypothesis test. Based on the SPSS calculation it found that the Sig (2 tailed) of pre-post test was lower than the minimum value of significance (.000 < 0.05) or tcount of pre-post test was higher than ttable (11.4 > 2.04 with df 30 and sig. value 0.025). So, Ho was rejected and Ha was accepted in turn, it also proved that there was significant effect of using EGRA technique on students’ ability in comprehending recount text.